Evidence for Impaired Neocortical Synaptic Plasticity in Bipolar II Disorder - Elvsåshagen, Torbjørn; Moberget, Torgeir; Bøen, Erlend; Boye, Birgitte; Englin, Nils O.A.; Pedersen, Per Ø.; Andreassen, Ole A.; Dietrichs, Espen; Malt, Ulrik F.; Andersson, Stein (Biological psychiatry (1969), 2012)
Synaptic plasticity might play an important role in the pathophysiology and treatment of bipolar disorders. There is, however, a paucity of human evidence supporting this hypothesis, mainly due to a lack of methods for noninvasive assessment of synaptic plasticity. It has recently been demonstrated that plasticity of the visual evoked potential (VEP) induced by repeated visual stimulation might reflect synaptic plasticity. In this study, we examined VEP plasticity in healthy control subjects and patients with bipolar II disorder (BD-II). Forty healthy control subjects and 26 individuals with a DSM-IV diagnosis of BD-II matched for age and gender participated. The VEPs were evoked by checkerboard reversal stimulation before and after a modulation block of prolonged (10 min) visual stimulation. The modulation block resulted in significant VEP plasticity in healthy control subjects. The VEP plasticity was significantly impaired in patients with BD-II. Explorative analyses indicated a trend toward a less severe impairment in medicated than in unmedicated patients. Visual evoked potential plasticity might represent a reliable and robust assay for studies of synaptic plasticity in vivo in humans. In addition, our findings support the hypothesis of impaired synaptic plasticity in BD-II. Longitudinal studies are needed to fully clarify the effects of medication and mood state on VEP plasticity.